Optimization of dose and image quality in CR and DR for common digital radiographic examinations - Moey, Soo Foon; Ahmad Shazli, Zubir (2018)
Radiological examinations known to have associated risk of induced malignancy and deterministic effects if over the threshold dose. Patient radiation doses should be kept as low as reasonably achievable.Ideal balance between image quality and patient radiation dose by optimization to minimize stochastic risks and prevention of deterministic effects.